(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
English language is realized as a link language with global significance and also the most spread language in the world. English is used not only for communicating with the outside world, but also for inter-state and intra-state communication. The ability to express our thoughts and ideas in English effectively is an art. Every student has to develop good communication skills to survive in the global market. It is the role of teacher to make them acquire those skills. Several methods and approaches have arrived in ELT and they keep on changing according to the learners’ needs.Communicative language teaching (CLT) is a very exciting development in the field of ELT. In the recent past, language teaching seems to have shifted the emphasis away from “accuracy” to “fluency” and from “structural competence” to “communicative competence”. This is one of the methods which suits to meet the learners’ needs in the present scenario.